Pengaruh Penggunaan Media Pembelajaran Animasi Terhadap Motivasi Belajar Siswa Pada Pembelajaran Pendidikan Agama SD Di Kota Padang - Putri, Ghima Septia; Alfurqan, Alfurqan (el-Ibtidaiy:Journal of Primary Education, 2023)
The use of instructional media is very important in the learning and teaching process because the media is also an inseparable unit from the world of education itself. Animation media is a learning media that contains a collection of images that produce movement and is equipped with audio so that it is memorable and keeps learning messages. This study aims to determine the effect of the use of animated media on students' learning motivation in learning Islamic religious education in elementary schools. This study used a quantitative method with an experimental type, the data source was taken from 27 respondents in grade 3 SDN 20 Kurao Pagang, Padang City. The results of the study as a whole show that there are four influences of animated media on student learning motivation, namely: learning activities go well, student scores increase before and after using animated media, analysis of the distribution of variable questionnaires student motivation is in the fairly high category, there is a significant influence linear between animation media on student learning motivation